Effect of tightening torque on the mechanical performance and damage form of hybrid bonded/bolted joints - SHEN Jinyi; HU Weixin; ZHANG Tianyu; HU Junshan; LIAO Wenhe; TIAN Wei; SHEN Ye (Jixie qiangdu)
To investigate the mechanical properties of woven composite hybrid bonded/bolted joints, a mechanical failure model for hybrid bonded/bolted joints based on 3D progressive damage model and cohesive force model was developed to simulate the mechanical behavior and damage evolution of the joints.Based on the Abaqus finite element software, a finite element simulation model for hybrid bonded/bolted joints woven composites was established. The damage initiation and propagation of the composite material were judged using the three-dimensional Linde criterion. The cohesive force model was used to simulate the damage failure process of the adhesive layer. On the basis of test verification of the model accuracy, the strength and damage failure process of the joints were analyzed under different tightening torques. The test and simulation results indicate that as the tightening torque increases, the extension of adhesive layer damage can be effectively suppressed. However, the shear strength of the adhesive layer in the hybrid bonded/bolted joints firstly increases and then decreases, because increasing the tightening torque can reduce the peeling stress of the adhesive layer in the joints. However, the excessive tightening torque will strengthen the stress around the adhesive layer hole, leading to a decrease in the shear srength of the adhesive layer and a decrease in the strength of the connection structure. The load-displacement curve of the numerical simulation is consistent with the test results, and the predicted adhesive layer fracture load is equivalent to the test results. At the same time, the fiber damage, matrix damage, and delamination damage on the laminated plate can also be well reflected in the numerical model, which is similar to the damage form after the connection test, verifying the effectiveness of the damage prediction model.